Double Distal Perfusion Catheters for Severe Limb Ischemia on the IABP Side in Patients Who Received Femoro-Femoral VA-ECMO With IABP - Xin, Meng; Wang, Liangshan; Tian, Xiaqiu; Hou, Dengbang; Wang, Hong; Wang, Jiangang; Jia, Ming; Hou, Xiaotong (Frontiers in Medicine, 2021)
Background: Limited research is available on the pattern of double distal perfusion catheters in patients on venoarterial extracorporeal membrane oxygenation (VA-ECMO)with an intra-aortic balloon pump(IABP). Here, we compared the outcomes of a double distal perfusion catheter and conventional treatment in patients who received VA-ECMO with IABP and had severe lower limb ischemia on the IABP side. Methods: We reviewed the data of 15 adult patients with postcardiotomy cardiogenic shock who received VA-ECMO via femoral cannulation combined with an IABP in the contralateral artery that was complicated with severe acute limb ischemia (ALI) on the same side as the IABP between January 2004 and December 2016. Patients underwent symptomatic treatment (conventional group, n=9) and double distal perfusion catheterization treatment (DDPC group, n=6). ALI was monitored using near-infrared spectroscopy placed on both calves after double distal perfusion catheters. The outcomes were compared. Results: All 6 patients who underwent double distal perfusion catheters were successfully decannulated without the development of osteofascial compartment syndrome, amputation, or bleeding and infection of the double distal perfusion catheters. The number of patients who weaned from extracorporeal membrane oxygenation successfully in the DDPC and conventional groups was 6 (100%) and 3 (33%, p=0.028), respectively. The in-hospital mortality rates were 17% and 89% for the DDPC and conventional groups, respectively (p=0.011). Conclusions: DDPC can be considered a strategy for severe limb ischemia on the IABP side in patients who received femoro-femoral VA-ECMO with IABP.